Marsh's Self-Description Questionnaire III (SDQ III): adaptation study with portuguese college students - Luísa Faria (1996)
The Self Description Questionnaire III (SDQ III) is one of a series of Australian self-concept instruments designed to measure self-concept of pre-adolescents (SDQ I), in early to middle adolescents (SDQ II), late adolescents and early adults (SDQ III). It was designed by Marsh (1988) and is based on the Shavelson, Hubner, and Stanton (1976) hierarchical and multidimensional model. This study presents the various steps followed in the adaptation of this Australian self-concept instrument using 691 Portuguese college students from Northern Portugal. In general the internal consistency of the instrument, assessed by Cronbach's alpha, proved to be good and similar to the Australian version, but the factorial structure of the Portuguese version revealed twelve factors instead of thirteen of the original scale. The presence of the global self-concept dimension in several factors questions its independence from the ether dimensions in the Portuguese version.